2013
DOI: 10.1073/pnas.1218353110
|View full text |Cite
|
Sign up to set email alerts
|

Lariat sequencing in a unicellular yeast identifies regulated alternative splicing of exons that are evolutionarily conserved with humans

Abstract: Alternative splicing is a potent regulator of gene expression that vastly increases proteomic diversity in multicellular eukaryotes and is associated with organismal complexity. Although alternative splicing is widespread in vertebrates, little is known about the evolutionary origins of this process, in part because of the absence of phylogenetically conserved events that cross major eukaryotic clades. Here we describe a lariat-sequencing approach, which offers high sensitivity for detecting splicing events, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(121 citation statements)
references
References 61 publications
6
114
0
Order By: Relevance
“…Previous attempts to experimentally determine branchpoints has relied on laborious, low-throughput RT-PCR or 2D-gel purification of lariats (Gao et al 2008;Awan et al 2013) or identified several hundred branchpoints from large-scale RNA-sequencing atlases (Taggart et al 2012;Bitton et al 2014). In contrast, RNA CaptureSeq and RNase R digestion significantly enrich for intron lariats, allowing genome-wide branchpoint detection in wild-type cells without blocking intron debranching (Bitton et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to experimentally determine branchpoints has relied on laborious, low-throughput RT-PCR or 2D-gel purification of lariats (Gao et al 2008;Awan et al 2013) or identified several hundred branchpoints from large-scale RNA-sequencing atlases (Taggart et al 2012;Bitton et al 2014). In contrast, RNA CaptureSeq and RNase R digestion significantly enrich for intron lariats, allowing genome-wide branchpoint detection in wild-type cells without blocking intron debranching (Bitton et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…First, the lariat intron will more effectively report on splicing events that result in NMD-sensitive mRNA isoforms (Awan et al 2013). Second, the lariat intron reports on splicing efficiently, because every read from a lariat intron reflects a splicing event.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of splicing from the perspective of excised introns, introns have been enriched by stabilization in a strain in which the gene DBR1 was deleted (Spingola et al 1999;Juneau et al 2007;Zhang et al 2007;Awan et al 2013;Bitton et al 2014;Stepankiw et al 2015); DBR1 encodes a debranchase that linearizes a lariat through hydrolysis of the unique 2 ′ -5 ′ phosphodiester bond-a prerequisite for rapid, exonucleolytic degradation (Chapman and Boeke 1991). Early microarray-based studies inferred the location of introns as those genomic regions in which RNA levels increased in the dbr1Δ strain, relative to a wild-type strain (Juneau et al 2007;Zhang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The mature circular RNA consisting of mrps16 exon 2 then accumulates in cells, while the double lariat from the re-splicing event and the skipped linear mRNA are both rapidly degraded. 41,88 Interestingly, there are other examples of exon skipping events in S. pombe, 89 yet none of these genes appear to generate circular RNAs. 41 This argues that the production of an exoncontaining lariat is not sufficient for circular RNA biogenesis, and the mechanisms by which cells determine when to re-splice to yield a circular RNA remain unclear.…”
Section: Circular Rnas Generated Via Exon Skippingmentioning
confidence: 99%